ANALISIS PROSPEKTIF DALAM LAPORAN KEUANGAN PERBANKAN: STUDI KASUS KINERJA KEUANGAN BANK JATIM PERIODE 2022 - Syaila Salsabila; Cyntya Dwi Permata; I Gede Agung Krisnha; Renny Oktafia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Prospective analysis is a forecasting process that can depict the financial performance of a banking institution. In this case study, the researcher will analyze the financial performance of Bank Jatim during the 2022 period. There are several factors that influence the financial performance of banking institutions, such as total asset growth, credit growth, customer deposit growth, and net interest income. In 2022, Bank Jatim showed improvement compared to the previous year. The financial performance of banking institutions is also influenced by economic conditions and monetary policies. In 2022, the increase in benchmark interest rates by the Federal Reserve and Bank Indonesia has led to a decline in the overall performance of marketable securities and significant pressure on trading performance. Prospective analysis will assist Bank Jatim in developing effective financial strategies and strengthening its financial performance position. In this case study, we will analyze the financial performance of Bank Jatim during the 2022 period. The financial performance of Bank Jatim is expected to continue to improve with increases in total assets, credit growth, customer deposit growth, and net interest income.